2019
DOI: 10.1096/fj.201900909rr
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ap2a2 in PPARα‐mediated regulation of lipolysis in adipose tissue

Abstract: Adipose tissue plays a major role in the regulation of systemic metabolic homeostasis, with the AP2 adaptor complex being important in clathrin-mediated endocytosis (CME) of various cell surface receptors, including glucose transporter 4, the insulin receptor, and b-adrenergic receptors (ARs). One of the AP2 subunits, adaptor-related protein complex 2, a2 subunit (Ap2a2), has recently been identified as a peroxisome proliferatoractivated receptor (PPAR)a target gene. The effects of PPARa on the AP2 adaptor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Interestingly, PPARα-dependent regulation of fatty acid oxidation in extrahepatic tissues plays an important role during fasting and can compensate, at least in part, for the absence of PPARα in hepatocyte-specific Ppara-null mice [261]. A role for adipose PPARα in the β-adrenergic regulation of lipolysis has been suggested [262]. Overexpression of PPARα in adipose tissue is associated with improvement in HFD-induced alterations in glucose metabolism, mostly through modulation of BCAA metabolism [263].…”
Section: Ppars In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Interestingly, PPARα-dependent regulation of fatty acid oxidation in extrahepatic tissues plays an important role during fasting and can compensate, at least in part, for the absence of PPARα in hepatocyte-specific Ppara-null mice [261]. A role for adipose PPARα in the β-adrenergic regulation of lipolysis has been suggested [262]. Overexpression of PPARα in adipose tissue is associated with improvement in HFD-induced alterations in glucose metabolism, mostly through modulation of BCAA metabolism [263].…”
Section: Ppars In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…PPARγ is highly expressed in healthy adipose tissue with important metabolic activities and functions in the regulation of adipocytokines secretion 19 . Although PPARα has been suggested to have a less pronounced role in adipose tissue, recent studies have shown that the activation of this transcription factor stimulates FAO, 30 mitochondrial biogenesis, oxidative capacity, 31 and activates lipolysis in adipose 32 . We observed that epididymal WAT (eWAT) from PPARα –/– mice had significantly lower levels of Ct‐1 mRNA expression than the WT animals (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been reported that defective PPARγ in adipocytes causes impairment in the catecholamine‐induced lipolysis due to a dysfunction of the PKA, as well as defects in the expression of major lipases and specific dysregulation of lipid droplet proteins 45 . Recently, it has been shown a novel role for PPARα in β‐adrenergic regulation of adipose tissue lipolysis 32 . In this sense, our data support the idea that physiological levels of CT‐1 are necessary in prolonged food restriction states to permit lipid mobilization and are in line with the concept that PPAR coordinates both catabolic and anabolic processes in the adipocyte and that these effects are fundamental to maintaining the metabolic flexibility required for the efficient management of nutritional fluxes in and out of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that many enzymes involved with fatty acid catabolism, TCA cycle flux and oxidative phosphorylation are expressed at significantly higher levels in GFAT adipocytes compared with VAT and ASAT adipocytes. PPARa is critical for the transcription of genes that translate proteins involved in adipocyte lipolysis, fatty acid oxidation and mitochondrial biogenesis, and PPARa agonists exert weight loss (Lazennec et al, 2000;Li et al, 2005;Montgomery et al, 2019;Shalev et al, 1996). PPARα-RXRα activation was over-represented in the GFAT adipocyte proteome and the enrichment of PPARα target pathways suggest that enhanced oxidative disposal of fatty acids may be a component underpinning the so-called 'safe' disposal of fatty acids in GFAT.…”
Section: Discussionmentioning
confidence: 99%